Voltage Stability Analysis of Grid-connected Photovoltaic Power Systems Using CPFLOW - Warut Suampun (My University, 2016)
This paper proposes a CPFLOW-based algorithm for analyzing voltage stability of grid-connected photovoltaic (PV) power systems. The main advantages of this algorithm are its computational speed and the ability to overcome the numerical difficulty near the point of voltage collapse. Using the proposed algorithm, a numerical study is conducted to analyze voltage stability of IEEE 14-bus and 39-bus systems under varying conditions. It is shown via numerical results that higher PV penetration levels can greatly improve the overall system voltage stability. An evaluation of PV installation locations also shows that each location on the grid has different degrees of suitability, regarding stability impact. Integrating PV generations at bad locations can cause serious degradation to system voltage stability.
Keywords: Power System Optimization and Stability